Edu-Game Sebagai Media Pembelajaran Pendidikan Anak Usia Dini Di Taman Kanak-Kanak Dharma Wanita 56 - Santika, Gayatri Dwi (Fakultas Teknik, Universitas PGRI Banyuwangi, 2021)
Educational games are very interesting to develop because of the visualization of real problems. Based on the pattern possessed by the game, players are required to learn so that they can solve existing problems. Game status, instructions, and tools provided by the game will guide players actively to explore information so that they can enrich their knowledge and strategies while playing. Development of mobile game applications as an alternative learning media to recognize symbols, count, match pictures and arrange random words as an alternative medium for early childhood education for teacher learning in changing conventional learning methods to learning simulation games, so as to develop children's creativity, because in educational games have elements of challenge, accuracy, reasoning and ethics.